2003
DOI: 10.1023/a:1023937123600
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract.We have found one reason why AdaBoost tends not to perform well on gene expression data, and identified simple modifications that improve its ability to find accurate class prediction rules. These modifications appear especially to be needed when there is a strong association between expression profiles and class designations. Cross-validation analysis of six microarray datasets with different characteristics suggests that, suitably modified, boosting provides competitive classification accuracy in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(2 citation statements)
references
References 41 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Otherwise, it keeps almost equal performance. Then we investigated the performance of the proposed method in a comparison of some popular classifiers including Support Vector Machine (SVM), K -Nearest Neighbors ( K NN), and AdaBoost which are widely used for gene expression data analysis [2729]. In that comparison, we used both simulated and real gene expression datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, it keeps almost equal performance. Then we investigated the performance of the proposed method in a comparison of some popular classifiers including Support Vector Machine (SVM), K -Nearest Neighbors ( K NN), and AdaBoost which are widely used for gene expression data analysis [2729]. In that comparison, we used both simulated and real gene expression datasets.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the proposed β -NBC outperforms existing robust linear classifiers as mentioned earlier. Then we investigate the performance of the proposed method in a comparison with some popular classifiers including Support Vector Machine (SVM), k -nearest neighbors ( K NN), and AdaBoost; those are widely used in gene expression data analysis [2729]. We observed that the proposed method improves the performance over the others in presence of outliers.…”
Section: Introductionmentioning
confidence: 99%